2015
DOI: 10.1080/01635581.2015.1015745
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Long-Chain Omega-3 Polyunsaturated Fatty Acids (LCω-3PUFA) and Prostate Cancer

Abstract: We conducted a systematic review and meta-analysis to estimate the potential association between LCv-3PUFAs and prostate cancer (PC). A comprehensive literature search was performed through 2013 to identify prospective studies that examined dietary intakes of long-chain omega-3 polyunsaturated fatty acids (LCv-3PUFA) or blood biomarkers of LCv-3PUFA status and risk of PC. Random-effects meta-analyses were conducted to generate summary relative risk estimates (SRREs) for LCv-3PUFAs and total PC, and by stage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 61 publications
1
17
0
5
Order By: Relevance
“…Cohort studies assessing the risk of PrCa mortality suggested an association between higher intake and decreased risk. The results of this review are consistent with other systematic reviews conducted, 70 , 71 which also assessed prevention and secondary PrCa outcomes using diet and supplement exposure and found no association.…”
Section: Discussionsupporting
confidence: 89%
“…Cohort studies assessing the risk of PrCa mortality suggested an association between higher intake and decreased risk. The results of this review are consistent with other systematic reviews conducted, 70 , 71 which also assessed prevention and secondary PrCa outcomes using diet and supplement exposure and found no association.…”
Section: Discussionsupporting
confidence: 89%
“…In the first meta-analysis previously referenced [ 14 ], five estimates of risk for breast cancer did not show a significant association, and no effects were found for cancers of the aero-digestive tract, bladder, colorectum, ovary, pancreas or stomach, or for lymphoma. While a recent study observed that high levels of serum phospholipid omega-3 FA (a biomarker) were associated with a large increase in the risk of high-grade prostate cancer [ 17 ], subsequent systematic review and meta-analysis, including 12 studies of self-reported dietary intake of omega-3 FA and 9 biomarker studies, failed to find an association between omega-3 FA and prostate cancer [ 18 ]. These ambiguities require clarification and undoubtedly will require randomized, double-blinded intervention trials.…”
Section: Introductionmentioning
confidence: 99%
“…Although the overwhelming weight of evidence supports beneficial effects of dietary n‐3 LC‐PUFA, there has been some negative reporting such as that on prostate cancer that impacted on sales of fish oil capsules for direct human consumption . However, a very recent meta‐analysis across approximately 20 studies did not support an association between n‐3 LC‐PUFA and prostate cancer . Other meta‐analyses studies have questioned the efficacy of n‐3 supplements for the secondary prevention of cardiovascular disease .…”
Section: Importance Of N‐3 Lc‐pufa In Human Healthmentioning
confidence: 99%